High‐grade radiologic extra‐nodal extension predicts distant metastasis in stage II nasopharyngeal carcinoma. Issue 9 (17th June 2019) - Hu, Yujun; Lu, Tianzhu; Huang, Shao Hui; Lin, Shaojun; Chen, Yunbin; Fang, Yanhong; Zhou, Han; Chen, Yiping; Zong, Jingfeng; Zhang, Yu; Chen, Ying; Pan, Jianji; et al.
Abstract: Background: To investigate the prognostic value of radiologic extra‐nodal extension (rENE) in stage II nasopharyngeal carcinoma (NPC). Methods: Stage II NPC patients with N1 category (n = 365) were enrolled and divided into three groups according to the situation of rENE: without rENE, suspected rENE, and confirmed rENE (grades: A, infiltration into surrounding fat; B, matted nodes; C, infiltration into adjacent structures). Results: Only high‐grade rENE (including matted nodes and infiltration into adjacent structures) could significantly influence the survival outcomes, patients with high‐grade rENE had significantly poorer survival than those without, with the 7‐year distant metastasis‐free survival and overall survival demonstrated to be 78.5% vs 93.0% ( P < .001) and 81.9% vs 89.9% ( P = .05), respectively. High‐grade rENE, as defined in our study, is a stable criterion, with high intra‐rater and inter‐rater consistency. Conclusion: High‐grade rENE was an evaluable predictor that could help with the selection of stage II patients with high risk of distant metastasis.